Need for Quantitative Measurement Methods for Posterior Uveitis: Comparison of Dual FA/ICGA Angiography, EDI-OCT Choroidal Thickness and SUN Vitreous Haze Evaluation in Stromal Choroiditis - Fabro, Filippo; Herbort, Carl P. (Klinische Monatsblätter für Augenheilkunde, 2018)
Background/Purpose Quantitative methods for posterior uveitis are necessary for precise appraisal and follow-up of inflammation in practice and in clinical trials. The aim of this study was to assess fluorescein angiography (FA), indocanine green angiography (ICGA), and enhanced depth imaging optical coherence tomography choroidal thickness (EDI-OCT CT) in two stromal choroiditis entities, birdshot retinochoroiditis (BRC), and Vogt-Koyanagi-Harada disease (VKH), as well as to determine (1) disease patterns, (2) respective response to therapy, and (3) their potential utility in clinical trials in comparison to vitreous haze, the present standard outcome used in clinical trials.Methods This retrospective study included newly diagnosed patients with BRC and VKH, seen at the Centre for Ophthalmic Specialized Care, Lausanne, Switzerland. Angiographic signs were quantified using an established dual FA/ICGA scoring system for uveitis at presentation and on follow-up. FA/ICGA score ratios were compared between diseases to determine disease patterns. EDI-OCT CT was determined using a spectral domain instrument. Vitreous haze was determined using the SUN (Standardization of Uveitis Nomenclature) method.Results Among 1872 uveitis patients seen from 1995 to 2016, 8 newly diagnosed BRC patients (16 eyes) and 6 newly diagnosed VKH patients (12 eyes) had sufficient data for study inclusion. Patients with BRC and VKH at initial onset had mean FA scores of 16.1 ± 7.0 vs. 4.6 ± 2.1 (p < 0.0001), respectively, while mean ICGA scores were similarly high in the two diseases, 18.9 ± 3.6 (BRC) vs. 20.8 ± 7.5 (VKH). After therapy, FA and ICGA scores decreased significantly for both entities (− 60% of FA score and 55% of ICGA score in BRC vs. − 72% of FA score and − 87% for ICGA score in VKH). EDI-OCT CT decreased significantly in the two entities. Vitreous haze was almost absent in VKH and low in BRC.Conclusion Dual FA/ICGA scoring showed the diverse disease patterns of BRC and VKH; both the retina and choroid were involved at onset in BRC, whereas VKH was a pure choroidal disease with later spillover into the retina. Dual FA/ICGA allowed for the precise measurement of inflammation at onset and upon follow-up. EDI-OCT CT responded to therapy in both diseases but was found to be of limited use in this early/subacute disease phase because it lacked sensitivity to detect subclinical recurrences and was therefore only useful for long-term follow-up. Vitreous haze was low in both entities and thus useless as an inflammatory parameter.
Keywords: Birdshot retinochoroiditis; Vogt-Koyanagi-Harada disease; stromal choroiditis; indocyanine green angiography; angiographic score; standardization of uveitis nomenclature (SUN)